CCDC22 mutations that impair COMMD binding cause attenuated 3C/Ritscher-Schinzel syndrome - Amika Singla; Carolyn Rogers; Mary-Joe Touma; Yassin El-Najjar; Alison Colley; Daniel J. Boesch; Daniel D. Billadeau; Jozef Gecz; Baoyu Chen; Ezra Burstein (BMC Medical Genomics)
Abstract The CCC complex, composed of CCDC22, CCDC93, and ten proteins of the COMMD family, coordinates several critical steps required to recycle internalized plasma membrane proteins from endosomes to the cell surface. CCC interacts with Retriever, a trimeric cargo recognition complex comprising VPS35L, VPS26C, and VPS29, and works closely with the WASH complex, a crucial regulator of branched actin polymerization at endosomal membranes. Mutations in genes encoding subunits of these three complexes, CCDC22, VPS35L, and WASHC5, have been linked with a developmental syndrome known as 3 C (cranio-cerebello-cardiac) or Ritscher-Schinzel syndrome. Here, we report a new CCDC22 missense mutation, p.E208K, that results in attenuated 3 C syndrome, without cardiac or neuroanatomical abnormalities. We show that this mutation impairs CCC complex assembly by disrupting a conserved interaction surface required for CCDC22-COMMD4 binding. We also review previously described cases and identify that CCDC22 p.P172R has a similar attenuated phenotype and impairs complex assembly in a similar fashion as p.E208K. The characterization of these mutations adds to our understanding of the clinical and molecular spectrum of these disorders.